Exploratory study on the efficacy of topical pan-JAK inhibitor in ocular and skin GVHD in a sclerodermatous GVHD mouse model - Shinri Sato; Yoko Ogawa; Kazuki Asai; Eisuke Shimizu; Shota Shimizu; Hiroko Taniguchi; Takahiro Okazaki; Shigeto Shimmura; Kazuno Negishi; Masatoshi Hirayama (Scientific Reports)
Abstract Systemic administration of Janus kinase (JAK) inhibitors is effective in treating chronic graft-versus-host disease (cGVHD) but is associated with side effects. Topical drug administration effectively minimizes side effects. We aimed to investigate potential trends of the efficacy of topical delgocitinib administration in a mouse model. Allogenic bone-marrow transplantation (BMT) was performed from B10.D2. to BALB/c mice, leading to sclerodermatous GVHD. GVHD mice were treated with delgocitinib eye drops or ointment with samples analyzed at 4 weeks post-BMT. Topical delgocitinib ointment and eye-drop administration significantly increased the meibomian gland (MG) area and attenuated corneal epithelial damage. Pathological and immunohistochemical analyses revealed a substantial reduction in inflammation and pathological fibrosis of the skin and eyelids in delgocitinib-treated GVHD mice. Signal transducer and activator of transcription (STAT)1, STAT3, and STAT5A phosphorylation was significantly increased in the back skin and eyelids of vehicle-treated GVHD mice; topical delgocitinib administration significantly reduced the expression of these phosphorylated STAT molecules. Delgocitinib eye drops significantly attenuated corneal epithelial damage, MG acinar depletion, and inflammatory cells infiltration in GVHD mouse corneas. The JAK/STAT signaling pathway was significantly upregulated in GVHD mice. In summary, our data suggested that topical delgocitinib administration had the potential to attenuate cGVHD phenotype severity in the skin and eyes of sclerodermatous GVHD mice.